2021
DOI: 10.1108/jea-03-2021-0065
|View full text |Cite
|
Sign up to set email alerts
|

Exploring trust: culturally responsive and positive school leadership

Abstract: PurposeThis article explores the connection between Culturally Responsive School Leadership (CRSL) and Positive School Leadership (PSL) and how both engage with a concept that deeply connects both leadership expressions – trust.Design/methodology/approachA multi-year, single site case study method examined a district-level equity leader, and her struggles and successes with promoting equity and positive culture throughout a large suburban district in the US.FindingsTrust, established through regular interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Bryk and Schneider (2002) concluded from their longitudinal study conducted in 400 Chicago elementary schools that relational trust fostered attachment to the school's mission and mitigated the feelings of risk that accompany substantive change. Likewise, Banwo et al. ’s (2021) five-year case study of social justice leadership found trust was necessary for stakeholders to form meaningful relationships, discuss inequitable practices and constructively address conflicts.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Bryk and Schneider (2002) concluded from their longitudinal study conducted in 400 Chicago elementary schools that relational trust fostered attachment to the school's mission and mitigated the feelings of risk that accompany substantive change. Likewise, Banwo et al. ’s (2021) five-year case study of social justice leadership found trust was necessary for stakeholders to form meaningful relationships, discuss inequitable practices and constructively address conflicts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Discourse within suburban contexts can default to a race-neutral, rational discourse that displaces discussions about competing priorities and perpetuates the status quo (Frankenberg and Kotok, 2013). Moving the community forward in equity initiatives may, therefore, require difficult conversations about race, socioeconomic status and power differentials to foster collective growth (Banwo et al. , 2021; Castro et al.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Relationships are critical to a president's ability to impact their university by integrating into its culture, getting to know people and operations, and creating a support base for pushing initiatives or responding to crises. This latter point is crucial to the progression of education as a field of study and an impactful experience for students (Banwo et al, 2022;Khalifa, 2019;Murphy & Louis, 2018). The connections made by the participants were at all levels of the university and beyond campus borders.…”
mentioning
confidence: 97%